THE EFFECTS OF BULLYING ON EARLY CHILDHOOD EMOTIONS AND ITS IMPACT ON PSYCHOLOGICAL DEVELOPMENT - Pratama, Muhammad Daffa; Wati, Vivi Widia; Fadhilah, Fadhilah; Syarifuddin, Syarifuddin; Safitri, Sani (Jurnal Kopendik, 2025)
Bullying is a social problem that continues to occur in Indonesia and can affect anyone regardless of age, place, or time. Forms of bullying can be verbal, physical, or psychological, each of which may cause serious harm, both physically and mentally. The psychological effects of bullying can disrupt the victims’ emotions, thoughts, and behaviors, thus influencing their social lives. This study aims to analyze the effects of bullying on early childhood emotions and its impact on their psychological development. The research method used is library research, which involves reviewing relevant literature related to bullying phenomena and children’s mental health. The results indicate that bullying leads to psychological disorders such as stress, anxiety, and decreased self-confidence, which affect children’s social adjustment. Therefore, the active role of parents and teachers is essential in providing character education, psychological rehabilitation, and creating a safe and supportive environment for children.